2020
DOI: 10.1155/2020/8814257
|View full text |Cite
|
Sign up to set email alerts
|

Field Tests of Super‐Long and Large‐Diameter Drilled Shaft Pile Foundations

Abstract: This study investigated the compressive behaviour of super-long pile foundations with large diameters. Three 52 m, 73 m, and 83 m long piles with a diameter of 1500 mm, 1500 mm, and 1800 mm were cast and tested, respectively. Given that large loading was required, an improved compressive static load test was introduced, and the load transfer mechanism, shaft resistance development, and distribution were analysed. This study found that the transferred load decreased along the pile during each applied load, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The Effect of Saturation Degree on Point Bearing Capacity Factor for Bored Piles in Sands 317 L=20m). Wang et al [69] observed that piles, whose diameters of 1.5-1.8m and lengths of 52-83m, were mobilized at settlement values of 55.5-87.4 mm corresponding to 2.5-6.0% of pile diameter. The normalized settlement values obtained in the laboratory were greater than the pile loading test results in the field.…”
Section: Load-settlement Behaviormentioning
confidence: 99%
“…The Effect of Saturation Degree on Point Bearing Capacity Factor for Bored Piles in Sands 317 L=20m). Wang et al [69] observed that piles, whose diameters of 1.5-1.8m and lengths of 52-83m, were mobilized at settlement values of 55.5-87.4 mm corresponding to 2.5-6.0% of pile diameter. The normalized settlement values obtained in the laboratory were greater than the pile loading test results in the field.…”
Section: Load-settlement Behaviormentioning
confidence: 99%